Ag–SiO2 nanocomposites with plum-pudding structure as catalyst for hydrogenation of 4-nitrophenol. Issue 10 (December 2015) - Shi, Yao; Zhang, Xiao-Liang; Feng, Gang; Chen, Xiangshu; Lu, Zhang-Hui
Abstract: Ag–SiO2 nanocomposites (NCs) with "plum-pudding" structure have been synthesized using a facile reverse micelle method. The as-synthesized Ag–SiO2 NCs were calcined at 623 K to remove the surfactants and then characterized by XRD, FE-SEM, TEM, EDX, ICP and N2 adsorption–desorption. The obtained results demonstrated that many ultrafine Ag nanoparticles (NPs) with size of ~2 nm are well dispersed in each SiO2 nanosphere (28 nm). In comparison with free Ag NPs and SiO2 supported Ag NPs, the Ag–SiO2 NCs exhibited a better catalytic activity for the reduction of 4-nitrophenol with a turnover frequency of 489 h −1 at room temperature. Ag–SiO2 NCs also displayed a superior catalytic activity for hydrogenation of 2-NP and 3-NP. The activation energy of Ag–SiO2 NCs was estimated to be about 34.4 kJ mol −1, which was lower than most of the reported values for the same reaction using Ag-based catalysts, indicating the superior catalytic performance of these plum-pudding structured catalysts.